EFFECTIVENESS OF FORMING A COLOR-LINGUISTIC VIEW OF THE WORLD IN PRIMARY CLASS STUDENTS (Scientific journal of the Fergana State University, 2023)
In this article, it has been studied that it is important to form the unique characteristics of the child's linguistic personality with a colorful landscape, the comprehensive development of primary school students, and the fact that speech is rich and flawless in the education of a mature generation